Public Organisations & Legitimacy: Gaps, Crises & Repair - Steingrímsdóttir,Hrafnhildur Jóna (2025)
Public organisations need legitimacy to operate and there are many ways for them to gain, maintain and repair it. Without legitimacy, public organisations can face challenges such as legitimacy gaps or crises, which can have lasting effects on their function and authority. This thesis aims to shed light on how public organisations in Iceland communicate when their legitimacy is questioned and what repair strategies they tend to use. Additionally, this thesis looks at news media sentiment as an indicator of how communication efforts are perceived and offers a valuable contrast between a legitimacy gap and crisis. The data for this project was collected through four semi-structured interviews with communication specialists or civil servants working in communication at different public organisations in Iceland, documents published by two of the organisations represented among the interviewees, and news media headlines. The material was analysed through a combination of Benoit's (2015) image repair theory and Suchman's (1995) legitimacy repair strategies framework, as well as a content analysis of news media headlines. The findings reveal that the four public organisations communicated in similar ways when their legitimacy was questioned, often relying on reframing situations by softening them, minimising their impact, and explaining constraints. News media headlines as an indicator of sentiment towards communication efforts revealed that some of the strategies chosen by the public organisations, such as minimising impacts and explaining constraints, could have adverse effects on perceptions, which in turn would hinder legitimacy repair efforts. By looking at both a legitimacy gap and a crisis, it was revealed that the two call for a different amount of communication efforts by public organisations, but it is difficult to differentiate between the two while they occur. Other notable themes include the revelation that Icelandic public organisational communicators might not think consciously about legitimacy as much as the literature suggests and that communication is often an afterthought in the public sector in Iceland. These findings indicate the practical value for Icelandic public sector organisations in considering and focusing on legitimacy-building and repair strategies as part of their communication initiatives and that a clearer alignment between communication strategies and the type of legitimacy threat faced may improve communication efforts.
Keywords: Organisational Legitimacy; Legitimacy Gap; Legitimacy Crisis; Public Administration; Legitimacy Repair; Image Repair; Communication Efforts; Media Sentiment